Controllable Fabrication of Ordered Mesoporous Bi2WO6 and Its High Photocatalytic Activity under Visible Light. (26th June 2014) - Dang, Xueming; Dong, Xiaoli; Wang, Hua; Zhang, Xiufang; Ma, Hongchao; Xue, Mang
Abstract : Ordered mesoporous Bi2 WO6 was fabricated by nanocasting technique using SBA-15 as the template. The effect of the dosage of SBA-15 on the formation of the ordered structure and the photocatalytic ability of mesoporous Bi2 WO6 was discussed. It was confirmed that the ordered mesoporous structure was obtained as the dosage of SBA-15 was 0.3 g. It was found that, compared to Bi2 WO6, the RhB degradation rate with ordered mesoporous Bi2 WO6 was enhanced under visible light (λ > 400 nm) by the photocatalytic measurements. The enhanced photocatalytic performance of ordered mesoporous Bi2 WO6 was attributed to its particular ordered mesoporous structure which could increase the light-harvesting efficiency, reduce the recombination of the photogenerated charge carriers, and promote the surface reaction.